Advancements and prospects of thermal management and waste heat recovery of PEMFC. (February 2021) - Baroutaji, Ahmad; Arjunan, Arun; Ramadan, Mohamad; Robinson, John; Alaswad, Abed; Abdelkareem, Mohammad Ali; Olabi, Abdul-Ghani
Highlights: The thermal management strategies of PEMFC are reviewed. The waste heat recovery pathways of PEMFC are presented. The challenges and prospects of the aforementioned areas are discussed. Abstract: Despite that the Proton Exchange Membrane Fuel Cell (PEMFC) is considered to be an efficient power device; around half of the energy produced from the electrochemical reaction is dissipated as heat due to irreversibility of the cathodic reaction, Ohmic resistance, and mass transport overpotentials. Effective heat removal from the PEMFC, via cooling, is very important to maintain the cell/stack at a uniform operating temperature ensuring the durability of the device as excessive operating temperature may dry out the membrane and reduces the surface area of the catalyst hence lowering the performance of the cell. In addition to cooling, capturing the produced heat and repurposing it using one of the Waste Heat Recovery (WHR) technologies is an effective approach to add a great economic value to the PEMFC power system. Global warming, climate change, and the high cost of energy production are the main drivers to improve the energy efficiency of PEMFC using WHR. This paper presents an overview of the recent progress concerning the cooling strategies and WHR opportunities for PEMFC. The main cooling techniques of PEMFCs are described and evaluated with respect to their advantages and disadvantages. Additionally, the potential pathways for PEMFC-WHR including heating, cooling, and power generation are explored and assessed. Furthermore, the main challenges and the research prospects for the cooling strategies and WHR of PEMFCs are discussed.